Spray-dried self-nanoemulsifying drug delivery systems as carriers for the oral delivery of piperine: Characterization and in vitro evaluation - Nindya Kusumorini, Akhmad Kharis Nugroho, Suwijiyo Pramono, Ronny Martien (Journal of Applied Pharmaceutical Science, 2022)
Piperine is the primary alkaloid compound of white pepper, which has many therapeutic benefits. However, piperine has limitations, including low bioavailability, being photosensitive, and being unstable in liquid preparations. This study aims to increase the dissolution rate and stability of isolated piperine in solid preparations using the solid- selfnanoemulsifying drug delivery systems (S-SNEDDS) formulation approach. The S-SNEDDS formulation was made with Miglyol 812 N, PEG400, and Cremophor RH40 as oil, cosurfactant, and surfactant with a ratio of 2.25:2.60:5.15, respectively. The S-SNEDDS solidification process used mesoporous mannitol as an inert adsorbent. It implemented the spray drying method. S-SNEDDS characterization was performed through droplet size distribution, vibration spectroscopy, morphological characteristics, thermal analysis, X-ray diffraction, and in vitro drug release. The characterization results showed no observed crystallization and interaction of isolated piperine with pore carriers in the S-SNEDDS formulation. It was confirmed by vibrational spectroscopy and thermal analysis. S-SNEDDS morphology results showed liquid-SNEDDS contained in mesoporous mannitol pore carriers. In addition, S-SNEDDS increased the dissolution rate of isolated piperine up to 10 times compared to pure isolated piperine. The S-SNEDDS formulation is helpful for dealing with active substances with low solubility and is photosensitive because of their ease of handling and flexibility for further formulation.
Keywords: Piperine, SNEDDS, S-SNEDDS, D-mannitol, mesoporous mannitol